Food Analysis Laboratory Manual - Nielsen, S. Suzanne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This third edition laboratory manual was written to accompany Food Analysis, Fifth Edition, by the same author. New to this third edition of the laboratory manual are four introductory chapters that complement both the textbook chapters and the laboratory exercises. The 24 laboratory exercises in the manual cover 21 of the 35 chapters in the textbook. Many of the laboratory exercises have multiple sections to cover several methods of analysis for a particular food component or characteristic. Most of the laboratory exercises include the following: background, reading assignment, objective, principle of method, chemicals, reagents, precautions and waste disposal, supplies, equipment, procedure, data and calculations, questions, and references. This laboratory manual is ideal for the laboratory portion of undergraduate courses in food analysis.
Laboratory Standard Operating Procedures -- Preparation of Reagents and Buffers -- Dilution and Concentration Calculations -- Use of Statistics in Food Analysis -- Nutritional Labeling Using a Computer Program -- Accuracy and Precision Assessment -- High Performance Liquid Chromatography -- Gas Chromatography -- Mass Spectometry with High Performance Liquid Chromatography -- Moisture Content Determination -- Ash Content Determination -- Fat Content Determination -- Protein Nitrogen Determination -- Total Carbohydrate by Phenol-Sulfuric Acid Method -- Vitamin C Determination by Indophenol Method -- Water Hardness Testing by Complexometric Determination of Calcium -- Phosphorus Determination by Murphy-Riley Method -- Iron Determination by Ferrozine Method -- Sodium Determination Using Ion Selective Electrodes, Mohr Titration, and Test Strips -- Sodium and Potassium Determinations by Atomic Absorption Spectroscopy and Inductively Coupled Plasma-Optical Emission Spectroscopy -- Standard Solutions and Titratable Acidity -- Fat Characterization -- Proteins: Extraction, Quantitation, and Electrophoresis -- Glucose Determination by Enzyme Analysis -- Gliadin Detection by Immunoassay -- Viscosity Measurements of Fluid Food Products -- CIE Color Specifications Calculated from Reflectance or Transmittance Spectra -- Extraneous Matter Examination -- Answers to Practice Problems.
Keywords: Food science; Chemistry, Technical; Spectrum analysis